Analysis of the Effect of Trotel Variations and Valve Load Variations on the Performance of Gasoline and Diesel Fuel Motors - Yazirin, Cepi; Raharjo, Artono (Universitas Merdeka Malang, 2024)
Technological developments in the modern era have experienced quite a significant increase, one of which is the combustion motorbike. Several things that are of concern to continue to be developed in combustion engines are the fuel system, ignition system and valve mechanism. The aim of this research is to analyze the effect of variations in throttle and valve load on petrol and diesel engines to determine the performance of these engines. The method used in this research is an experimental method by providing throttle variations and valve load variations on petrol and diesel motorbikes. The results of this research are that on petrol motorbikes the throttle changes with a fixed load at Pi, Pm, Ni, Ne, Nm, Qe, ηe, and ηi. There is a correlation between rotation and throttle, where the higher the rotation and the larger the throttle, the higher the value of the throttle. Pi, Pm, Ni, Ne, Nm, Qe, ηe, and ηi. In diesel motors Pi, Pm, Ni, Ne, Nm, Gs, Gg, Qb, Qeg, Qe, Qpp, ηe, and ηi There is a correlation between rotation and throttle, where the higher the rotation and the larger the throttle, the higher the value of Pi. , Pm, Ni, Ne, Nm, Gs, Gg, Qb, Qeg, Qe, Qpp, ηe, and ηi.